The current state of studies of the optical properties of semiconductive materials - Федотов, Вячеслав Віталійович (Technology audit and production reserves, 2014)
It is analyzed the optical properties of semiconductors due to the fact that the research of nonlinear optical effects in semiconductors is increased an interest, both in terms of basic science as well as in terms of the huge prospects for practical use of research results in the creation of new quantum electronics devices. As a result of this analysis it was found the major dependence of refraction, absorption and reflection from radiation wavelength. The dependence between the intensity of the incident beam and the intensity of output (such reflected or passing through a semiconductor) beam with consideration of absorption (reflection) of the material is determined. In results of absorption coefficient study of the material on free charge carriers it is appeared that it depends not only on the wavelength and refractive index, but also on factors such as the electron density and mobility of charge carriers.